The Semantic Association in the Mental Lexicon - Gopee Krishnan; Shivani Tiwari (Journal of All India Institute of Speech and Hearing, 1970)
The organization of mental lexicon has been extensively debated and discussed in the contemporary psycholinguistics. Specifically, this study investigated into the nature of organization of semantically related and unrelated concepts in the mental lexicon. A group of 19 participants (age range: 17-23 years; 11 females & 8 males) was required to judge the semantic association between the word pairs presented through reaction time software (DMDX). The participants judged the semantically associated word pairs faster compared to the semantically unrelated pairs. This finding could be explained by the Spreading activation theory of lexical processing (Collins & Loftus, 1975; Dell, 1986). The semantic features that are in common to the words of the stimulus pairs received double activation and this facilitated a faster judgment in the case of semanticallyassociated word pairs compared to unassociated word pairs.